Guest

prove that x^(logy-logz).y^(logz-logx).z^(logx-logy)=1

prove that x^(logy-logz).y^(logz-logx).z^(logx-logy)=1

Grade:11

1 Answers

Arun
25758 Points
4 years ago
Dear Ritish
 
x^ log y- log z + y^ log z - log x + z ^ log x - log y
introducing log to each term,
log x ^ ( log y- log z) + log y^ (log z - log x) + log z ^ (log x - log y)
= log x ( log y- log z) + log y (log z - log x) + log z (log x - log y)
= log x log y - log x log z + log y log z - log x log y + log x log z -log y log z
=0 
= log 1
removing log from both sides we have ,
x^ log y- log z + y^ log z - log x + z ^ log x - log y = 1
 
Regards
Arun (askIITians forum expert)

Think You Can Provide A Better Answer ?

Provide a better Answer & Earn Cool Goodies See our forum point policy

ASK QUESTION

Get your questions answered by the expert for free